2022
DOI: 10.3389/fendo.2021.815386
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Glucocorticoid Receptor Actions in Bone Homeostasis and Bone Diseases

Abstract: Glucocorticoids (GCs) are steroid hormones that respond to stress and the circadian rhythm. Pharmacological GCs are widely used to treat autoimmune and chronic inflammatory diseases despite their adverse effects on bone after long-term therapy. GCs regulate bone homeostasis in a cell-type specific manner, affecting osteoblasts, osteoclasts, and osteocytes. Endogenous physiological and exogenous/excessive GCs act via nuclear receptors, mainly via the GC receptor (GR). Endogenous GCs have anabolic effects on bon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 95 publications
(144 reference statements)
0
11
0
Order By: Relevance
“…The main pathological cause of GIOP is an imbalance of bone homeostasis between osteoblastic bone formation and osteoclastic bone resorption ( 23 ). Previous studies indicated that GCs resulted in bone impairment by reducing osteoblast differentiation, promoting the apoptosis of osteoblasts and osteocytes, and prolonging the life span of osteoclasts ( 2 , 23 ). Furthermore, GCs can affect bone metabolism by regulating canonical Wnt-β-catenin and OPG/RANKL/RANK signaling, respectively ( 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…The main pathological cause of GIOP is an imbalance of bone homeostasis between osteoblastic bone formation and osteoclastic bone resorption ( 23 ). Previous studies indicated that GCs resulted in bone impairment by reducing osteoblast differentiation, promoting the apoptosis of osteoblasts and osteocytes, and prolonging the life span of osteoclasts ( 2 , 23 ). Furthermore, GCs can affect bone metabolism by regulating canonical Wnt-β-catenin and OPG/RANKL/RANK signaling, respectively ( 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…Namely, in this study, all included cases of ONFH were steroid induced. It has already been well established that glucocorticoids directly affect bone metabolism, greatly enhancing osteoclastic bone resorption and inhibiting osteogenesis 15,16 . As a monoclonal antibody against receptor‐activator of nuclear factor κ‐B ligand (RANKL), denosumab could promote the apoptosis of osteoclasts and inhibit the bone resorption induced by osteoclasts, 17,18 which might be the predominant reason for femoral head collapse in patients with steroid ONFH 18 .…”
Section: Discussionmentioning
confidence: 99%
“…Obviously, the use of some medications to treat co-morbidities could also influence outcomes depending on the type and dosages being used. Treatment with anti-inflammatory medications, such as NSAIDS [ 67 , 68 , 69 ] or high or continuous doses of glucocorticoids [ 70 , 71 ], could potentially adversely affect outcomes after interventions with cell therapy approaches. Therefore, the presence of co-morbidities and their treatment, as well age and sex, should be recognized and addressed before initiating interventions to enhance the repair/regeneration of injured connective tissues of the MSK system.…”
Section: Factors That Can Complicate Post-injury Processes and Inflam...mentioning
confidence: 99%